2018
DOI: 10.11005/jbm.2018.25.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Is Sarcopenia a Potential Risk Factor for Distal Radius Fracture? Analysis Using Propensity Score Matching

Abstract: BackgroundCases of low-energy-induced distal radius fracture (DRF) are increasing. Sarcopenia is considered to be an independent risk factor for fragility fractures. We compared body appendicular lean muscle mass (ALM) and bone mineral density (BMD) in patients with DRF and a comparable control population. This study aimed to investigate the correlation between skeletal muscle mass and DRF.MethodsWe performed a retrospective review of patients diagnosed with fragility DRF. The DRF group included 87 patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This study identified the risk factors for tibial plateau fractures combined with intercondylar eminence fractures, which included patients who were aged over 74 years and retired. The findings are consistent with other investigations. Lee et al .…”
Section: Discussionsupporting
confidence: 94%
“…This study identified the risk factors for tibial plateau fractures combined with intercondylar eminence fractures, which included patients who were aged over 74 years and retired. The findings are consistent with other investigations. Lee et al .…”
Section: Discussionsupporting
confidence: 94%
“…While the incidence of hip and shoulder fractures increases after the age of 80, the incidence of DRFs increases at age 60–70 and therefore affects more active elderly individuals [ 5 ]. Lee et al [ 6 ] previously reported that patients with DRF do not have significantly lower average lean body mass but that bone mineral density (BMD) is significantly lower in patients with DRF. Some reports have suggested that low body mass is a risk for hip fracture [ 7 , 8 ] and that patients with DRF have a preserved body mass compared with patients with hip fracture.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Roh et al 6 showed that sarcopenia rates were higher in patients with DRF than age- and sex-matched controls. In contrast to that study, Lee et al 7 demonstrated that appendicular lean mass and sarcopenia rates were not significantly different between patients with DRF and age- and sex-matched controls. Nevertheless, these studies defined sarcopenia according to only dual-energy X-ray absorptiometry (DEXA) results, other sarcopenia components demonstrating muscle function (handgrip strength, walking time) have not been considered.…”
Section: Introductionmentioning
confidence: 60%